Optimization of Media for Antimicrobial Activity of Enterobacter sp. Associated with Entomopathogenic Nematode Rhabditid sp. - Sangeetha, B G; Jayaprakas, C A; Jithine, J R; Mohandas, C (JOURNAL OF ROOT CROPS, 2017)
An entomopathogenic bacterium isolated from the nematode, Rhabditis ( Oscheius ) sp. was found to produce secondary metabolites with antimicrobial activity. Media for the production of the bioactive metabolites were standardized with tryptic soya broth (TSB) supplemented with six carbon sources viz., glycerol, maltose, fructose, glucose, sucrose and lactose. Antimicrobial activity was found highest for culture filtrate solvent extract (CFSE) obtained from TSB plus glycerol combination. Among the different carbon sources tested, glycerol proved to be the best for antimicrobial activity and that was followed by maltose, fructose and glucose. Media with lactose and sucrose combination had the least antimicrobial activity. A high degree of variation in the level of antimicrobial activity against the test organism viz., Fusarium oxysporum MTCC 284, Rhizoctonia solani MTCC 4634, Penicillium expansum MTCC2006, Aspergillus flavus MTCC 183, Candida albicans MTCC 277 was observed. The present study revealed that the source of carbon has a pivotal role in the production of antimicrobial activity.